Assessing genetic relatedness of in vitro cassava accessions using morphological traits and DArTseq single nucleotide polymorphism (SNP) markers - Byiringiro, M.H.; Uchendu, E.E.; Paliwal, R.; Abberton, M. (2025)
Genetic diversity is crucial for breeding progress and maintenance of biodiversity. This study assessed the genetic relatedness of 101 in vitro cassava (Manihot esculenta Crantz) accessions from the International Institute of Tropical Agriculture (IITA), Genetic Resources Centre, in February 2023 up to March 2024. The objective was to evaluate phenotypic and genotypic diversity, identify potential duplicates, and provide insights for improved genebank management and breeding strategies. Morphological traits (plant height, root length, number of roots per plant, number of leaves per plant, leaf length, leaf width, and lobe number) were quantified weekly for four weeks post-meristem subculture, commencing one week after subculture. Genome-wide SNP markers were generated using the DArTseq Genotype-by-Sequencing approach, yielding 19,467 high-quality SNPs. Analysis of Variance (ANOVA) of morphological traits revealed significant differences (p < 0.01) of all traits across accessions and weeks. Root length and number of leaf lobes had significant differences (p < 0.01) across accessions and weeks. Cluster analysis identified four distinct clusters based on morphological traits. Cluster II held the most accessions while Clusters I and IV had the least, indicating phenotypic variation patterns primarily driven by root morphology, plant architecture, and leaf traits. Principal Component Analysis (PCA) revealed that the first three components explained 67.26% of the total variation among accessions. The leaf length (LL), Leaf width (LW), Number of roots per plant (NR), Plant height (PH), and Root Length (RL) had the highest eigenvalues of − 0.551, − 0.531, − 0.398, − 0.383, and − 0.298, respectively, in PC1. A strong positive correlation (r = 0.81***) was observed between leaf width and leaf length. Phylogenetic analysis using 19,467 SNPs identified four distinct genetic groups within the cassava population. Molecularly, PCA revealed that the first three PCs explained 15, 4.74, and 3.7% of the genetic variation. Phylogenetic and PCA analyses yielded consistent results, confirming the robust nature of the identified genetic structure. The SNP markers are effective for evaluating genetic diversity and identifying duplicates in the cassava collection. These results from molecular and morphological analysis revealed a consistent genetic diversity and potential duplicates among the accessions, which may arise not only from contamination but also from outcrossing of ancestors, given the diverse germplasm maintained at IITA. This study has important implications for cassava genebank management, quality control, conservation strategy, germplasm exchange, and future breeding efforts.